The Burial of the Guns - Page, Thomas Nelson, 1853-1922 (Salt Lake City, UT : Project Gutenberg, 2008)
"The Burial of the Guns" by Thomas Nelson Page is a historical fiction novel likely written in the late 19th century. It delves into the aftermath of the Civil War, focusing on the emotional and social ramifications of surrender and the transition back to civilian life, particularly through the experiences of Southern soldiers and their commanders. The opening introduces readers to complex characters, such as the old Colonel and his battery of soldiers, who grapple with pride, duty, and the loss of their former identities as they face the end of the war. At the start of the narrative, the story revolves around the old Colonel and his battery stationed at a crucial mountain pass after the war's conclusion. As soldiers adjust to the fact that General Lee has surrendered at Appomattox, the Colonel's leadership is put to the test. He faces the painful decision of preventing their guns from being captured, reflecting on the bonds formed between the men throughout the war. The opening conveys this sense of duty and camaraderie as the Colonel prepares to bury the guns to preserve their legacy, while the soldiers express their sorrow at their collective fate and their commitment to uphold the values they fought for within the new landscape of their post-war life. (This is an automatically generated summary.)
My cousin Fanny -- The burial of the guns -- The gray jacket of "No. 4" -- Miss Dangerlie's roses -- How the captain made Christmas -- Little Darby.
Release date is 2008-07-02
Produced by A. Light, Sherrie Settle and David Widger
Keywords: Short stories; United States -- Social life and customs -- 19th century -- Fiction